Identification of Patients with Early HR+ HER2- Breast Cancer at High Risk of Recurrence - Fasching, Peter; Kreipe, Hans; Del Mastro, Lucia; Ciruelos, Eva; Freyer, Gilles; Korfel, Agnieszka; Chouaki, Nadia; Stoffregen, Clemens; Sapunar, Francisco; Cameron, David (Geburtshilfe und Frauenheilkunde, 2024)
Breast cancer incidence has increased in the last two decades and, simultaneously, survival has improved due to earlier detection and improved treatment options. Despite this improvement, locoregional recurrences and distant metastases occur in up to 10 and 30% of women diagnosed with early breast cancer, respectively. Around 70% of breast cancers are hormone receptor positive (HR+), human epidermal growth factor receptor 2 negative (HER2-), and associated with a persistent risk of relapse up to 20 years after diagnosis/initial treatment. We conducted a narrative review by combining PubMed searches with our clinical experience to describe patient characteristics, biomarkers, and genomic profiling tools available to clinicians for the identification of patients with HR+, HER2- early breast cancer at high risk of recurrence and to provide recommendations to classify patients into recurrence risk categories. National and international treatment guidelines are also summarised. Accurate assessment of the risk of recurrence in these patients is crucial as the predicted risk guides treatment decisions; imprecise estimations can result in over- or undertreatment, with either scenario having negative consequences for patients. Multiple prognostic tools and factors are recommended for early breast cancer, and no single test provides accurate prognosis in isolation. Since no single test can provide accurate prognosis in isolation, a combination of tools should be used. Risk thresholds are important to guide optimised and balanced therapeutic decisions in HR+, HER2- early breast cancer. However, prognostic assessment should be performed on a case-by-case basis, making patient-specific prognostic approaches essential to avoid over- or undertreatment.
CRIS-Team Scopus Importer:2024-12-16
Keywords: early breast cancer; HER2-; HR+; prediction of risk; risk of recurrence